ANALISIS PENGARUH KEMUDAHAN PAYLATER PADA APLIKASI SHOPEE DAN PROMO DISKON PRODUK TERHADAP PERILAKU PEMBELIAN IMPULSIF (Studi pada Pengguna Shopee di DKI Jakarta) - Dhanty, Widya Rama; Cahyati, Annisa Vini; Alexandra, Esther Tiara (Jurnal Manajemen & Bisnis Jayakarta, 2022)
This study aims to determine and analyze the effect of ease of payment on the Shopee platform and product discount promos on the impulsive buying behavior of Shopee users in DKI Jakarta. Ease of payment and product discount promos as independent variables while impulse buying as the dependent variable. This research uses a descriptive quantitative approach which is analyzed using multiple linear analysis test with SPSS 26.0 data processing program. The population in this study were 150 residents of DKI Jakarta who used Shopee. Sampling data collection method using a questionnaire method. The results of the T-test (partial) of ease of payment and product discounts show that the value of T table > T arithmetic is -4.875 > 1.976 & 5.215 > 1.976. Meanwhile, the results of the F test (simultaneous) with the calculated F value > F table are 19.766 > 3.06. Which means that there is an influence of ease of payment and product discount promos on the impulsive buying behavior of DKI Jakarta residents using Shopee.